OVARIAN FOLLICULAR DYNAMICS DURING IMMEDIATE POSTINSEMINATION PERIOD AND SUBSEQUENT CONCEPTION IN GIR AND CROSSBRED CATTLE - HADIYA, KK; DHAMI, AJ; PATEL, JA; LUNAGARIYA, PM; SHAH, SV (The Indian Journal of Animal Reproduction, 2022)
Transrectal ultrasonography aided ovarian follicular dynamics of 20 cattle (9 Gir, 11 Crossbred) during 21-day post-insemination period was investigated to know the differences in cattle that subsequently conceived or failed to conceive. During this period, two follicular waves were observed in majority (p>0.05) of conceived (Gir, 66.7%; Crossbred, 80.0%) as compared to their non-conceived (Gir, 50.0%; Crossbred, 66.7%) counterparts. The linear growth and regression rate of 1st dominant follicle as well as the maximum diameter of 2nd dominant follicle were lower (p<0.05) in conceived cattle of both breeds compared to non-conceived cattle. Further, in the conceived crossbred counterparts, the 1st dominant follicle had delayed (p<0.05) beginning of regression phase (15.7±0.2 vs. 14.0±0.4 d) of shorter duration (4.7±0.6 vs. 7.0±0.4 d) as compared to non-conceived counterparts. In brief, a differential ovarian follicular dynamics exists during immediate post-AI period in dairy cattle.